Cement-based grout material and its application method

The cement-based grout material with lithium nitrite additives maintains quality in cold temperatures, addressing frost damage issues and reducing the need for large-scale curing enclosures and heat supply.

JP7608030B2Active Publication Date: 2025-01-06NIPPON KOATSU CONCRETE +1
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2021542599
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-23
Filing Date
2020-07-07
Publication Date
2025-01-06
Estimated Expiration
2040-07-07

AI Technical Summary

Technical Problem

Cement-based grout materials used in cold environments suffer from frost damage and strength loss due to freezing, necessitating large-scale curing enclosures and heat supply, which are costly and inefficient.

Method used

A cement-based grout material containing lithium nitrite at specific weight ratios (3-10% for -5°C and 4.5-8% for -10°C) is used, allowing construction without large-scale equipment by maintaining curing temperature through heat supply or curing.

Benefits of technology

Prevents freezing and ensures quality of cement-based grout in cold environments, reducing costs and effort by eliminating the need for extensive curing enclosures and fuel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608030000010
    Figure 0007608030000010
  • Figure 0007608030000011
    Figure 0007608030000011
  • Figure 0007608030000012
    Figure 0007608030000012
Patent Text Reader

Abstract

The present invention provides a cement grout material which does not freeze even in an environment where the ambient temperature can be -5°C or less, thereby ensuring the quality, and which does not require a fuel or large equipment such as a curing enclosure for maintaining the curing temperature. According to the present invention, lithium nitrite is added to a cement grout material that contains cement, water and an admixture. By setting the weight ratio of the lithium nitrite to the cement to a value from 3% by weight to 10% by weight, freezing of the grout material is able to be prevented so as to ensure the quality without using large equipment for maintaining the curing temperature or a fuel for heating even in an installation environment where the ambient temperature can be -5°C during the initial stage of installation. By setting the weight ratio of the lithium nitrite to a value from 4.5% by weight to 8% by weight, freezing of the grout material is able to be prevented so as to ensure the quality without using large equipment for maintaining the curing temperature or a fuel for heating even in an installation environment where the ambient temperature can be -10°C during the initial stage of installation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cement-based grout material and its application method that can ensure quality without freezing, even in environments of -5°C or below, without requiring large-scale curing equipment or heating means. [Background technology]

[0002] Materials whose main component is cementitious grout are widely used, for example, as filling small gap ducts placed inside structures such as bridges, dams, and buildings, as repair materials for narrow areas, and as grout filling sheaths into which PC steel bars of prestressed concrete are inserted (hereinafter referred to as "PC grout"). However, when the water in cementitious grout that has not yet hardened immediately after filling or repair is exposed to temperatures below freezing, it freezes. Cementitious grout that contains frozen water suffers from a quality degradation phenomenon known as frost damage, such as a significant decrease in strength.

[0003] In addition, the period when the daily average temperature is below 4°C is defined as cold weather, and depending on the region and period, there is a risk that the cementitious grout used as PC grout material may freeze, so it is standard practice not to inject PC grout material. If construction in cold weather is unavoidable, the cementitious grout material may freeze and not obtain sufficient strength, or the cementitious grout material may freeze and expand, causing cracks in the surrounding concrete.

[0004] Therefore, the Japan Society of Civil Engineers' Standard Specifications for Concrete stipulate that the temperature of the duct and surrounding area must be kept above 5°C before the PC grout is injected, and as a general rule, it should be kept above 5°C for at least three days after injection.

[0005] To prevent such frost damage, for example, in areas such as Hokkaido and Tohoku region of Japan where temperatures drop below zero (0°C) in winter, protective enclosures are set up and heat supply equipment such as jet heaters are used to maintain a heat supply and insulation curing state until a strength that is considered to be unaffected by frost damage is obtained. However, in order to maintain a heat supply and insulation curing state for ducts and repaired parts, which are part of a building in cold regions, it is necessary to set up a large-scale protective enclosure that covers the entire building or most of it, and the fuel costs for the heat supply equipment are enormous and often excessive compared to the amount of cement-based grout material used.

[0006] Patent Documents 1 to 7, for example, are inventions relating to PC grout materials and to cement and concrete used in cold regions.

[0007] Patent Document 1 describes a method of constructing prestressed concrete by the post-tensioning method in which cement grout is injected and filled into a sheath in a cold environment of below 0°C, in which cement grout containing an admixture consisting of 1 part by weight of a high-performance water reducing agent and 3 to 10 parts by weight of nitrite or a mixture of nitrite and nitrate, at 1 to 5% by weight relative to cement, is injected into a sheath provided within a concrete structure to fill it, and no measures are taken to prevent the cement grout from freezing after the injection and filling.

[0008] Examples of nitrites and nitrates mentioned include alkali metal salts such as ammonium salts, sodium salts, potassium salts, and alkaline earth metal salts such as calcium salts.

[0009] Patent Document 2 describes a method for inhibiting corrosion of PC tendons in post-tensioned PC structures, in which water is supplied to the space in the sheath where no grout is filled to remove or reduce the chloride ions present in the sheath and in the rust layer, the water is then removed, and the space from which the water has been removed is filled with grout.

[0010] Patent Document 3 describes a PC grout to be injected into the sheath of a PC structure, which contains nitrite as an anti-corrosive material and a powder containing CaO·2Al2O3 mixed into Portland cement as a chloride ion fixing material.

[0011] Patent Document 4 describes cold-resistant concrete containing an antifreeze agent mainly composed of lithium nitrite and an air-entraining agent or air-entraining water-reducing agent for generating fine air bubbles.

[0012] Patent Document 5 describes an antifreeze cement additive consisting of an alkali metal polycarboxylate or an alkaline earth metal polycarboxylate, in which the alkali metal is potassium, sodium, or lithium, or the alkaline earth metal is calcium.

[0013] Patent Document 6 describes a cement composition containing paraffin and nitrite as a cement composition having excellent salt damage suppression effect and excellent durability.

[0014] Patent Document 7 describes a durability improver for concrete that contains at least a shrinkage-reducing agent, paraffin, and a nitrite, which is capable of suppressing the decrease in the freeze-thaw resistance of concrete even when the agent contains a shrinkage-reducing agent and has a high shrinkage-reducing effect. The nitrite is described as being at least one selected from calcium nitrite, lithium nitrite, sodium nitrite, potassium nitrite, magnesium nitrite, barium nitrite, beryllium nitrite, zinc nitrite, and strontium nitrite. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Japanese Patent Publication No. 60-164556 [Patent Document 2] Japanese Patent Publication No. 2013-002056 [Patent Document 3] Japanese Patent Publication No. 2017-206418 [Patent Document 4] Japanese Patent Application Publication No. 10-259050 [Patent Document 5] Japanese Patent Application Publication No. 2007-119268 [Patent Document 6] Japanese Patent Application Publication No. 2015-202994 [Patent Document 7] Japanese Patent Publication No. 2018-140889 Summary of the Invention [Problem to be solved by the invention]

[0016] The invention described in Patent Document 1 involves adding a mixture using nitrite to cement grout, but when calcium nitrite is added, it hardens quickly when mixed and has poor fluidity, making it difficult to inject and fill it into the sheath as PC grout. Also, sodium nitrite and other nitrites can cause an alkali-aggregate reaction, making it difficult to apply in negative environments (below 0°C).

[0017] The invention described in Patent Document 2 uses lithium nitrite as an anti-rust agent to suppress corrosion of PC tendons, but does not take into consideration use in environments below 0°C or strength.

[0018] The invention described in Patent Document 3 also contains nitrite as a rust inhibitor and fixes chloride ions with CaO·2Al2O3, but like the invention described in Patent Document 2, does not take into consideration use in environments below 0°C or strength.

[0019] The inventions described in Patent Documents 4, 5, and 7 are intended for concrete and cannot be used as, for example, PC grout.

[0020] The invention described in Patent Document 6 is directed to incorporating paraffin and nitrite into a cement composition in the hope of inhibiting salt damage in concrete structures, but is not intended for use as cold weather concrete.

[0021] Under the above-mentioned circumstances, the present invention aims to provide a cement-based grout material and an application method thereof, which can ensure quality without freezing even in an environment where the outside temperature may be -5°C or lower, and which does not require large-scale equipment such as a curing enclosure to maintain the curing temperature, or fuel. [Means for solving the problem]

[0022] As a result of extensive research to achieve the above-mentioned object, the inventors have discovered that a cement-based grout material to which a specific amount of lithium nitrite has been added can ensure sufficient quality during construction in cold weather without the need for measures against frost damage, and have completed the present invention.

[0023] That is, the present invention provides 1. A cement-based grout material comprising cement, water, and an admixture, the cement-based grout material being characterized in that lithium nitrite is added to the cement-based grout material, and the weight ratio of the lithium nitrite to the weight of the cement is 3 to 10% by weight. 2. The cement-based grout material according to claim 1, characterized in that the cement-based grout material is a cement-based grout material for cold weather intended for use in a construction environment in which the outside air temperature at the initial stage of construction may drop to -5°C. 3. A cement-based grout material comprising cement, water and an admixture, the cement-based grout material being characterized in that lithium nitrite is added to the cement-based grout material, and the weight ratio of the lithium nitrite to the weight of the cement is 4.5 to 8% by weight. 4. The cement-based grout material according to 3, characterized in that the cement-based grout material is a cement-based grout material for cold weather intended for use in a construction environment in which the outside air temperature at the initial stage of construction may drop to -10°C. 5. The cement-based grout material according to 1, characterized in that the cement-based grout material is intended for use in a highly corrosive environment of steel materials due to chloride ions. 6. A method for applying a cementitious grout material comprising cement, water, and an admixture, the cementitious grout material having lithium nitrite added thereto, the weight ratio of the lithium nitrite to the weight of the cement being 3 to 10% by weight, the method being characterized in that curing or heating is performed so as to maintain the application environment at a location where the cementitious grout material is applied at -5°C or higher. 7. A method for applying a cementitious grout material comprising cement, water, and an admixture, the cementitious grout material having lithium nitrite added thereto, the weight ratio of the lithium nitrite to the weight of the cement being 4.5 to 8% by weight, the method being characterized in that curing or heating is performed so as to maintain the application environment at the location where the cementitious grout material is applied at -10°C or higher. to provide. Effect of the Invention

[0024] By using the cement-based grout material of the present invention, the extensive curing and fuel that were previously required as countermeasures against frost damage are no longer necessary, and the labor and costs can be significantly reduced. If the weight of lithium nitrite is added at 3 to 10% by weight relative to the weight of cement, it can be used as is even in an environment of -5°C. Also, if the weight of lithium nitrite is added at 4.5 to 8% by weight relative to the weight of cement, it can be used as is even in an application environment of -10°C.

[0025] Furthermore, according to the method for applying the cement-based grout material of the present invention, for example, in applying the cement-based grout material in an application environment where the outside temperature may drop below 0°C, by adding 3 to 10% by weight of lithium nitrite to the cement, it is possible to prevent the applied grout material from freezing and ensure its quality without using large-scale equipment such as a curing enclosure to maintain the curing temperature or fuel for heat supply to the application environment down to -5°C, and in the case where the outside temperature falls below -5°C, it is possible to prevent the grout material from freezing and ensure its quality by performing curing or heat supply to maintain the application environment at the location where the cement-based grout material is applied at -5°C or higher.

[0026] In addition, by adding 4.5 to 8% by weight of lithium nitrite to the cement, it is possible to prevent the applied grout material from freezing and ensure quality, without the need for large-scale equipment such as a curing enclosure to maintain the curing temperature down to a construction environment of -10°C, or fuel for heat supply.If the construction environment drops below -10°C, the grout material can be prevented from freezing and quality can be ensured by curing or supplying heat to maintain the construction environment at the location where the cement-based grout material is applied at -10°C or higher. [Brief description of the drawings]

[0027] [Figure 1] 1 is a graph showing the relationship between the weight ratio of lithium nitrite to cement and compressive strength when the curing temperature was −5° C. in Test 2 on the cement-based grout material according to the present invention. [Diagram 2] 1 is a graph showing the relationship between the weight ratio of lithium nitrite to cement and compressive strength when the curing temperature was −10° C. in Test 3 on the cement-based grout material according to the present invention. [Diagram 3] FIG. 1 is a diagram showing an outline of a method for preparing a specimen in Test 4 on the cement-based grout material according to the present invention. [Figure 4] FIG. 1 is a diagram showing an outline of a specimen for the accelerated corrosion test in Test 4. [Diagram 5]FIG. 1 is a diagram showing an outline of a method for measuring natural potential in an accelerated corrosion test in Test 4. [Figure 6] 13 is a graph showing the relationship between the spontaneous potential and the addition rate of lithium nitrite in Test 4. [Figure 7] FIG. 13 is a diagram showing an overview of a prestressed concrete injection specimen in Test 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The present invention is a cement-based grout material containing cement, water, and an admixture, characterized in that lithium nitrite is added, and the weight ratio of lithium nitrite to the weight of cement is 3 to 10% by weight.

[0029] When lithium nitrite is added to a cement-based grout material, there is a risk of the strength of the grout material decreasing. However, in the present invention, lithium nitrite is used within a range in which the grout material satisfies the standard strength and quality.

[0030] As the admixture, for example, commercially available high viscosity admixtures made from melamine sulfonic acid compounds for cement grout materials, water-soluble polymer ether compounds, etc., can be suitably used, but are not limited thereto.

[0031] The cement to be used may be, for example, ordinary Portland cement, high-early-strength cement, or blended cement, but there is no limitation on the type of cement as long as there are no problems with quality or durability when lithium nitrite is added.

[0032] Lithium nitrite may be added in the form of an aqueous solution or a solid. The concentration of the aqueous solution is not important. However, the concentration of the aqueous solution is usually about 5 to 43% by weight, and from the viewpoint of handling, 25 to 40% by weight is preferable.

[0033] The cementitious grout material of the present invention can be used, for example, as a PC grout material in the construction of prestressed concrete in cold regions during the coldest season, and can be used even in cold construction environments as cold as -5°C by adding 3 to 10% by weight of lithium nitrite to the cement.

[0034] In other words, assuming use in a construction environment where the outside air temperature at the beginning of construction can drop to -5°C, by adding 3 to 10% by weight of lithium nitrite to the cement, it is possible to prevent the applied grout material from freezing and ensure quality, without the need for large-scale equipment such as a curing enclosure to maintain the curing temperature or fuel for heat supply.

[0035] Assuming that the construction environment will drop to -5°C in the early stages of construction, if the amount of lithium nitrite added to the cement is less than 3% by weight, the standard strength of PC grout is generally required to be 30N / mm 2 may not be obtained.

[0036] In addition, even if the amount of lithium nitrite added to the cement is more than 10% by weight, the standard strength of 30 N / mm2, which is generally required for PC grout within 28 days, is not achieved. 2 may not be obtained.

[0037] If the outside temperature is predicted to drop below the initial assumption shortly after construction, protective enclosures and heating will be required to maintain an environment equivalent to -5°C or higher. However, compared to when using conventional grout materials, the costs of installing protective enclosures and heating equipment can be significantly reduced.

[0038] In addition, assuming use in a construction environment where the outside temperature at the beginning of construction can drop to -10°C, adding 4.5 to 8% by weight of lithium nitrite to the cement can prevent the applied grout material from freezing and ensure quality, without the need for large-scale equipment such as a curing enclosure to maintain the curing temperature or fuel for heat supply.

[0039] Assuming that the construction environment will drop to -10℃ in the early stages of construction, if the amount of lithium nitrite added to the cement is less than 4.5% by weight, the standard strength of PC grout is generally required to be 30N / mm 2 may not be obtained.

[0040] In addition, even if the amount of lithium nitrite added to the cement is more than 8% by weight, the standard strength of 30 N / mm2, which is generally required for PC grout within 28 days, is not achieved. 2 may not be obtained.

[0041] If the outside temperature is predicted to drop below the initial assumption shortly after construction, protective enclosures and heating will be required to maintain an environment equivalent to -10°C or higher. However, compared to when using conventional grout materials, the costs of installing protective enclosures and heating equipment can be significantly reduced.

[0042] Furthermore, as described above, the cementitious grout material of the present invention has the effect of significantly reducing the costs associated with installing protective enclosures and heating equipment when applied in environments where the outside temperature may drop to -5°C or below, compared to the application of conventional grout materials. Furthermore, as will be described in detail later, it has been experimentally confirmed that the hardened cementitious grout material of the present invention also has excellent anti-corrosion effects on steel materials in environments where they are exposed to chloride ions (for example, the anti-corrosion effects on PC steel wires placed within a sheath filled with grout material).

[0043] The method for applying a cement-based grout material of the present invention is a method for applying a cement-based grout material comprising cement, water, and an admixture, in which lithium nitrite has been added and the weight ratio of the lithium nitrite to the weight of cement is 3 to 10% by weight, characterized in that, for example, in applying the cement-based grout material in an application environment where the outside air temperature may drop to -5°C or lower, curing or heating is performed so as to maintain the application environment at the location where the cement-based grout material is applied at -5°C or higher.

[0044] As described above, by adding 3 to 10% by weight of lithium nitrite to cement, the applied grout material can be prevented from freezing and quality can be ensured without using large-scale equipment such as a curing enclosure to maintain the curing temperature down to a construction environment of -5°C or without using fuel for heat supply. Therefore, when the outside temperature falls below -5°C in the construction environment, the grout material can be prevented from freezing and quality can be ensured by curing or supplying heat to maintain the construction environment at the location where the cement-based grout material is applied at -5°C or higher.

[0045] Although there is no particular upper limit for curing or heating, in the case of the blending of the cementitious grout material of the present invention, the required quality can be maintained even at temperatures below 5°C, which is considered to affect the quality of ordinary cementitious grout materials, so that when the outside air temperature drops to below -5°C, curing or heating can be performed to keep the temperature substantially above -5°C and below 5°C or below 0°C. "Substantially" means that there may be a situation where the temperature falls temporarily outside this range due to temperature adjustment.

[0046] In addition, by adding 4.5 to 8% by weight of lithium nitrite to the cement, the applied grout material can be prevented from freezing and quality can be ensured without the need for large-scale equipment such as a curing enclosure to maintain the curing temperature down to a construction environment of -10°C or without the use of fuel for heat supply. Therefore, when the outside temperature falls below -10°C, the grout material can be prevented from freezing and quality can be ensured by curing or supplying heat to maintain the construction environment at the location where the cement-based grout material is applied at -10°C or higher.

[0047] In this case, for example, when the outside air temperature drops to -10°C or below, curing or heating can be carried out so as to maintain the temperature substantially at -10°C or above and below 5°C, or at 0°C or below -5°C. EXAMPLES

[0048] Hereinafter, Tests 1 to 3 relating to the cement-based grout material according to the present invention, and a comparative test in which calcium nitrite, which is the same nitrite, was used instead of lithium nitrite, will be described.

[0049] [Test 1] In Test 1, a performance test was conducted simulating use in a construction environment where the outside temperature drops to -10°C during the initial stages of construction.

[0050] The materials used in Test 1 are as follows: Cement: Ordinary Portland cement. Lithium nitrite: 40% by weight lithium nitrite solution in water. Admixture: Non-bleeding, high viscosity type high performance cement grout, admixture for injection mortar (product name "Masterflow 152" manufactured by BASF Japan Ltd., "Masterflow" is a registered trademark of Construction Research and Technology GmbH). Table 1 shows the mix proportions for Test 1. In Table 1, W is the unit water content, C is the unit cement content, and W / C is the water-cement ratio.

[0051] [Table 1]

[0052] In Test 1, quality inspections were conducted on the performance of PC grout based on the PC grout fluidity test method (JSCE-F531), PC grout material separation resistance test method (JSCE-F534), PC grout bleeding rate and volume change rate test method (JSCE-F535), chloride ion content test, and PC grout compressive strength test method (JSCE-G531). Table 2 shows the test results.

[0053] [Table 2]

[0054] In a rheology test of PC grout, the time was 15.7 seconds when lithium nitrite was added at 5.25% by weight, and 15.2 seconds when it was added at 9.0% by weight, both of which were within the range of the judgment criteria. In a material separation resistance test of PC grout, no bleeding was observed when lithium nitrite was added at 5.25% by weight and 9.0% by weight, and there were no problems with material separation resistance.

[0055] In the bleeding rate test of PC grout, the results were 0% when the lithium nitrite was added at 5.25% by weight and 9.0% by weight, below the judgment standard of 0.3%. The results of the volume change rate test were -0.33% when the lithium nitrite was added at 5.25% by weight and 9.0% by weight, below the judgment standard of -0.5% to 0.5%.

[0056] In the chloride ion content test, when the amount of lithium nitrite added was 5.25% by weight, the chloride ion content was 0.320 kg / m 3 , 0.311 kg / m for 9.0% by weight 3 The criterion is 1.0 kg / m 3 was within the range.

[0057] In the compressive strength test of PC grout, the lithium nitrite content of 5.25% by weight was 35.5N / mm2 , 32.5N / mm for 6.0% by weight 2 The standard is 30N / mm 2 However, in the case of 2.68% by weight, the result was 9.0 N / mm 2 , and 29.0N / mm for 9.0% by weight 2 The standard is 30N / mm 2 The result was below.

[0058] [Comparative Test] As a comparative test, a performance test was conducted assuming that calcium nitrite was used instead of lithium nitrite in a construction environment where the outside temperature drops to -10°C in the early stages of construction.

[0059] The materials used in the comparative tests are as follows: Cement: Ordinary Portland cement. Calcium nitrite: A 30% by weight aqueous solution of calcium nitrite was used, and the calcium nitrite was converted into 2.5%, 4.36%, and 6.2% by weight of the cement. Admixture: Same as Test 1. Table 3 shows the mix for the comparative test, and Table 4 shows the compressive strength test results for the comparative test.

[0060] [Table 3]

[0061] [Table 4]

[0062] From the compressive strength test in Table 4, when calcium nitrite was added at 2.5% by weight, the compressive strength was 1.15 N / mm 2 , 1.10N / mm for 4.36% by weight 2 , 2.19N / mm for 6.2% by weight 2 The standard is 30N / mm 2The results were significantly lower than those of the control, confirming that the addition of calcium nitrite to cement-based grout materials is not desirable in an environment of -10°C.

[0063] In the flowability test (rheology test) of PC grout, the time was 18.8 seconds when calcium nitrite was added at 2.5% by weight, 29.6 seconds when it was added at 4.36% by weight, and it was impossible to measure when it was added at 6.2% by weight, all of which were outside the range of the judgment criteria. When the grout was added at 6.2% by weight, the flowability was so significantly impaired that it would not fall even when scooped with a spoon and tilted.

[0064] [Test 2] Next, regarding the addition of lithium nitrite, which was confirmed to be effective in Test 1, the relationship between the amount of lithium nitrite added to cement and compressive strength was examined. In accordance with the compressive strength test method for PC grout (JSCE-G531), cylindrical specimens with a diameter of 5 cm x 10 cm were prepared and cured in air at -5°C for 28 days. The compressive strength test was carried out three times for each type of specimen, and the average value was calculated. The same non-bleeding, high-viscosity, high-performance cement grout and injection mortar admixture as in Test 1 was used as the admixture. The base formulation without added lithium nitrite is as shown in Table 5.

[0065] [Table 5]

[0066] The materials used in Test 2 were the same as those in Test 1, and in addition to the base formulation, 15 different amounts of lithium nitrite were added as shown in Table 6.

[0067] Table 6 shows the test results of compressive strength at 28 days after air curing at -5℃. Figure 1 shows the weight ratio of lithium nitrite to cement and the average value of compressive strength No. 1 to 3 in a bar graph.

[0068] [Table 6]

[0069] Looking at the average compressive strength from Table 6 and Figure 1, when the amount of lithium nitrite added to the cement was 0.5% by weight, the average compressive strength was 4.4 N / mm 2 , 5.1N / mm for 1.0% by weight 2 , 20.9N / mm for 2.0% by weight 2 and standard strength 30N / mm 2 Visual observation of these specimens revealed that the water in the unhardened grout appeared as an ice phase on the surfaces and cut surfaces of the specimens, which suggests that the frozen water had a detrimental effect on the hydration reaction.

[0070] However, when the amount of lithium nitrite added was 3.0% by weight of cement, the strength was 46.9 N / mm 2 and standard strength 30N / mm 2 When the amount of lithium nitrite added is up to 10.0% by weight of cement, the standard strength is 30 N / mm 2 The compressive strength exceeded 100%.

[0071] Then, when the amount of lithium nitrite added to the cement is 11.0% or 12.0% by weight, the standard strength is 30 N / mm 2 The result was below.

[0072] From the above, it can be seen from Test 2 that if the amount of lithium nitrite added is 3-10% by weight of cement, the standard compressive strength is 30N / mm 2 It was found that the temperature exceeded 100°C and that it could be used without any problems even in an environment of -5°C.

[0073] [Test 3] Next, the specimens were cured in air at -10℃ for 28 days to examine the relationship between the amount of lithium nitrite added to the cement and the compressive strength. Cylindrical specimens measuring Φ5cm x 10cm were prepared and tests were conducted in accordance with the compressive strength test method for PC grout (JSCE-G531). The compressive strength test was conducted three times for each type of specimen and the average value was calculated. The same non-bleeding, high-viscosity, high-performance cement grout and injection mortar admixture as in tests 1 and 2 was used as the admixture.

[0074] Table 7 shows the test results of compressive strength at 28 days after air curing at -10°C. Figure 2 shows the weight ratio of lithium nitrite to cement and the average value of compressive strength No. 1 to 3 in a bar graph.

[0075] [Table 7]

[0076] From Table 7 and Figure 2, the average compressive strength is 4.1 N / mm when the amount of lithium nitrite added is 2.0% by weight of cement. 2 , 8.5N / mm for 3.0% by weight 2 , 9.3N / mm for 3.5% by weight 2 , 10.8N / mm for 4.0% by weight 2 The standard strength is 30N / mm 2 The result was below.

[0077] In addition, when the amount of lithium nitrite added to the cement was 0.5% by weight and 1.0% by weight, the strength was insufficient and compressive strength tests could not be performed. Visual observation of these specimens revealed that the water in the unhardened grout appeared as an ice phase on the surface and cut surfaces of the specimens, which is thought to be the result of freezing of the water, and therefore it is believed that the freezing of the water had an adverse effect on the hydration reaction.

[0078] However, when the amount of lithium nitrite added was 4.5% by weight of cement, the strength was 39.1 N / mm 2 and standard strength 30N / mm 2When the amount of lithium nitrite added is up to 8.0% by weight of cement, the standard strength is 30N / mm 2 The compressive strength exceeded 100%.

[0079] Then, when the amount of lithium nitrite added is 9.0% to 12.0% by weight of cement, the standard strength is 30 N / mm 2 The result was below.

[0080] From the above, it was found from Test 3 that if the amount of lithium nitrite added to the cement is 4.5 to 8% by weight, the standard compressive strength is 30 N / mm 2 It was found that the temperature exceeded the limit and that it could be used without any problems even in an environment of -10°C.

[0081] Next, Tests 4 and 5 regarding the rust-preventing effect of the cement-based grout material according to the present invention will be described.

[0082] [Test 4] In Test 4, an accelerated corrosion test was conducted using a specimen simulating the eccentricity of a PC steel rod in a sheath filled with grout, with the aim of confirming the effect of grout containing lithium nitrite in inhibiting steel corrosion in a severe corrosive environment influenced by seawater and sea breeze.

[0083] The material used was a high-viscosity grout material, and the lithium nitrite addition rates were set at 3 wt%, 6 wt%, and 9 wt%, and compared with a case where no lithium nitrite was added.

[0084] Table 8 shows the grout materials and concrete mix factors, experimental conditions, and experimental items used in the test. The salt content of the concrete was 12 kg / m 3 The test method was accelerated corrosion testing (in accordance with JCI-SC3 of the Japan Concrete Institute).

[0085] [Table 8]

[0086] The test specimens were designed to simulate a condition in which chloride ions penetrated the concrete surface, causing corrosion damage to the steel sheath and exposing the grout material to chloride ions.

[0087] First, as shown in Figure 3, PC steel rod 2 (φ26 mm) was eccentrically placed inside steel sheath 1 (φ45 mm), and grout material containing a specified amount of lithium nitrite was filled in, after which the sheath was sealed and cured in an environment of 20°C for up to 28 days (Figure 3(a) state). After that, the component sheath 1 was completely removed to simulate corrosion damage (Figure 3(b) state).

[0088] Next, it was inserted into a prescribed position (cover 20 mm) within a formwork of φ100 × 200 mm, salt-containing concrete 4 was poured into it, and the formwork was removed when it was aged 2 days. It was then sealed and cured for aged 28 days and used for the accelerated corrosion test (state (c) in Figure 3).

[0089] An overview of the accelerated corrosion test is shown in Figure 4. The accelerated corrosion test was conducted in accordance with JCI-SC3 "Accelerated corrosion test method for reinforcing steel bars in salt-containing concrete - repeated wet-dry method" and consisted of up to 10 cycles of repeated wet-dry cycles, with one cycle consisting of a wet period (temperature 70°C, relative humidity 90%) for three days and a dry period (humidity 15°C, relative humidity 65%) for four days.

[0090] After each cycle, the natural potential of the PC steel rod 2 was measured. As shown in FIG. 5, the natural potential of the PC steel rod 2 was measured by a potentiometer 6 using a reference electrode 5 placed at the minimum cover (20 mm) position of the PC steel rod 2.

[0091] Figure 6 shows the relationship between the natural potential and the rate of lithium nitrite addition. The average value of the data obtained at the end of 10 cycles for the sample without lithium nitrite addition was -291 mV. VS On the other hand, the lithium nitrite addition rate of 3 to 9 wt% is -180 mV VS CSE~-153mV VSThe values ​​were 38 to 48% higher than those of CSE and the non-additive sample. These results confirmed the rust-prevention effect of the grout material containing lithium nitrite in a corrosive environment affected by chloride ions.

[0092] [Test 5] In Test 5, in order to confirm the rust-preventive performance under general environments, grout material containing added lithium nitrite was injected into prestressed concrete specimens, and a rust-preventive performance confirmation test was conducted by outdoor exposure.

[0093] Figure 7 shows an overview of the prestressed concrete injection test specimen. The test specimen 11 was 600 mm wide, 400 mm high and 15,700 mm long, with a φ35 mm steel sheathed pipe 12 placed inside the cross section and one PC steel strand (IS21.8 mm) inserted. One end of the upper and lower steel sheathed pipes 12 was connected by a hose 13, and grout material was injected and discharged from the other end. A thermometer 14 was embedded in the centre of the test specimen 11.

[0094] The lithium nitrite addition rates were set at 5.0% and 9.0% by weight, and the results were compared with a case where no lithium nitrite was added. The test was carried out at an outdoor test site. 96 days after grout injection, the test specimen was divided into 12 sections and exposure began. A rusting survey, in which the occurrence of rust on the cross sections was visually confirmed, was carried out on 11 cross sections 56 days after the start of exposure. The relationship between the lithium nitrite addition rate and the degree of rust formation is shown in Table 9. The degree of rust formation is calculated assuming that the area of ​​rust when no lithium nitrite is added is 1.0.

[0095] [Table 9]

[0096] If the rusting degree without lithium nitrite added is 1.0, the rusting degree with 9.0% lithium nitrite added is 0.44, and with 5.0% lithium nitrite added is 0.57, which means the rusting area was reduced by 43-56%. From these results, it was confirmed that the rust prevention effect of adding lithium nitrite is achieved even in an environment where chloride ions are not supplied.

Claims

1. A method for constructing a cement-based PC grout material for use in cold weather, which is intended for use in a construction environment in which the outside air temperature at the beginning of construction may drop to -5°C, the method comprising the steps of: adding lithium nitrite to the cement-based grout material, a weight ratio of the lithium nitrite to the weight of the cement being 3-10% by weight; and having a compressive strength of 30 N / mm2 or more at a material age of 28 days; and, when the outside air temperature falls below -5°C, curing or heating is performed to maintain the construction environment at the location where the cement-based grout material is constructed at -5°C or higher.

2. A method for constructing a cement-based PC grout material for use in cold weather, which is intended for use in a construction environment in which the outside air temperature at the beginning of construction may drop to -10°C, the method comprising the steps of: curing or supplying heat to a construction environment in which the construction environment at the location where the cement-based grout material is constructed is maintained at -10°C or higher when the outside air temperature falls below -10°C; and

Citation Information

Patent Citations

  • Construction of prestressed concrete by post tension construction method

    JP1985164556A

  • Hydrauric composition

    JP1989076936A

  • Method for preventing deterioration of hardened concrete

    JP1989103970A

  • Cement composition for placing during freezing weather

    JP1994234556A

  • Concrete resistant to cold

    JP1998259050A